Pain Vision System for Evaluating Chronic Pain: A Comparison with VAS Scoring - Bao-Kai Wang; Tang-Hua Liu; Fang Xie; Yan-Qing Liu (Pain Research and Management)
Objective. To study the value of pain vision system in quantitative evaluation of chronic pain from the perspective of neuroelectrophysiology, as compared with VAS (visual analog scale). Methods. Seventy-one patients with chronic pain were randomly selected to receive pain treatments from August 1, 2018, to September 30, 2018, in the Pain Department of Li Zhuang Tongji Hospital. Among all patients, 26 had cervical spondylosis and 45 had lumbar disc herniation. Pain vision and visual analog scoring (VAS) were used to evaluate the degree of pain before and after treatment. The correlation between the pain vision system’s pain ratio (pain ratio) and the VAS score was analyzed. Results. Pain ratio and VAS scores were linearly correlated before and after treatment in patients with chronic pain (Pearson coefficient was 0.730 before treatment and 0.449 after treatment; P<0.001). Conclusions. The pain vision system can evaluate chronic pain well and quantify it in the form of pain degree, which is helpful for objective quantitative analysis of chronic pain. This trial is registered with ChiCTR1900026331.